Human spaceflight and exploration - Norberg, Carol (Springer Praxis Books, 2013)
·         Covers the history of human spaceflight and exploration; ·         Reviews the challenges that the space environment poses on space missions; ·         Assesses spacesuit designs and their future development; ·         Details the selection and training of astronauts; ·         Discusses the success of the US Space Shuttle program in relation to the experiences of European astronaut Gerhard Thiele's personal account of flying aboard the Space Shuttle on a mission to map the Earth; ·         Considers the design of life support systems and future technologies   The book presents a unique overview of international activities in human spaceflight and exploration at a time of uncertainty regarding the direction of future development in the western world. It provides an introduction for the general public interested in space and would also be suitable for students at university. The contributors include a space physicist, two space engineers, a space-suit designer and two astronauts, who collectively have a broad experience of space activities.